Dimethyl Sulfoxide (DMSO) Decreases Cell Proliferation and TNF-α, IFN-γ, and IL-2 Cytokines Production in Cultures of Peripheral Blood Lymphocytes - De Abreu Costa, Lucas; Henrique Fernandes Ottoni, Marcelo; Dos Santos, Michaelle; Meireles, Agnes; Gomes de Almeida, Valéria; De Fátima Pereira, Wagner; Alves de Avelar-Freitas, Bethânia; Eustáquio Alvim Brito-Melo, Gustavo (Molecules (Basel, Switzerland), 2017)
Dimethylsulfoxide (DMSO) is an amphipathic molecule composed of a polar domain characterized by the sulfinyl and two nonpolar methyl groups, for this reason it is able to solubilize polar and nonpolar substances and transpose hydrophobic barriers. DMSO is widely used to solubilize drugs of therapeutic applications and studies indicated that 10% v/v concentration did not modify culture viability when used to treat human peripheral blood mononuclear cells (PBMC). However, some DMSO concentrations could influence lymphocyte activation and present anti-inflammatory effects. Therefore, the objective of this study was to evaluate the effect of DMSO on lymphocyte activation parameters. Cell viability analysis, proliferation, and cytokine production were performed on PBMC from six healthy subjects by flow cytometry. The results indicated that 2.5% v/v DMSO concentrations did not modify lymphocytes viability. DMSO at 1% and 2% v/v concentrations reduced the relative proliferation index of lymphocytes and at 5% and 10% v/v concentrations reduced the percentage of total lymphocytes, cluster of differentiation 4+ (CD4+) T lymphocytes and CD8+ T lymphocytes interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α) and interleukin-2 (IL-2) producers. Thus, it was concluded that DMSO has an in vitro anti-inflammatory effect by reducing lymphocyte activation demonstrated with proliferation reduction and the decrease of cytokine production.